Optimal taxation in asset markets with adverse selection - Seyed Mohammadreza Davoodalhosseini (Bank of Canada, 2020)
Constrained efficiency is characterized in an asset market, subject to search frictions, where sellers are privately informed about the type of their asset. The type determines the opportunity cost of the asset for sellers and the quality of the asset for buyers. The constrained efficient allocation can be implemented using a sales tax schedule. The role of these taxes is to redistribute resources between different types of sellers to relax incentive constraints. The optimal tax schedule strictly increases welfare compared with the laissezfaire equilibrium, can sometimes lead to an allocation that Pareto dominates the equilibrium, and can sometimes lead to the first-best allocation (i.e., taxation can correct all inefficiencies caused by adverse selection). The shape of the optimal tax schedule is also investigated. If the quality of assets for buyers is a monotonic function of the sellers' opportunity cost (e.g., more distressed sellers have lower-quality assets), the schedule requires that the trading of low-quality assets be subsidized and trading of high-quality assets be taxed, although the schedule is not necessarily monotone in the quality or price of the assets. Otherwise, trading of some lowquality assets may be taxed and trading of some high-quality assets may be subsidized.
Keywords: D82; D83; E24; G10; J31; J64; 330; Economic models; Financial markets; Financial system regulation and policies; Marketstructure and pricing